Central giant cell granuloma of mandible: a case report - Jaishri Pagare , Dr.; Gayatri Kale , Dr. (International Journal of Dental Research, 2024)
Central Giant Cell Granuloma(CGCG) and giant cell tumour of jawbone are grouped underneath same umbrella but with distinct clinical behavior. CGCG is a rare benign lesion of the jaws distinguish by the presence of multinucleated giant cells within a fibrous stroma. The pathogenicity of CGCG still remains an enigma, which demands the differentiation from other look-alike lesions in order to have proper diagnosis and treatment planning.  In this article, a case of CGCG in a 30-year-old female patient who presented with complaints of gradually increasing swelling and discomfort in the mandible is described.